Comparisons between nine-banded armadillo (Dasypus novemcinctus) populations in Brazil and the United States - Loughry, W J (Universidad de Costa Rica, 1998)
We compared characteristics of a population of nine-banded armadillos (Dasypus novemcinctus) studied in the soulhem Uniled States with a population found in the Atlanlic coastal rainforest of Brazil. Adult armadillos in Brazil weighed less than Ihose in Ihe U.S., but when weight was accounted for, did not differ in: other measures of body size. However, juveniles in Ihe U.S. were proportionately bigger!han Ihose in Brazil. Armadillos in Brazil were less abundant (numbers sighted per h of observation) and were active laler al night .!han Ihose in the U.S. Adult sex-ratios were male-biased in bolh populations: Finally, there was no significant difference in Ihe incidence of litterrnate associations observed in Ihe two populations, but groups of juveniles (which included non-Iitterrnates) were observed more frequently in tbe U.S. Many of Ihese differences may be due 10 the fact that armadillos are hunted extensively in Brazil but not in the United States.